Pengaruh Karakteristik Debitur, Tingkat Suku Bunga, dan Jangka Waktu Pinjaman Terhadap Kredit Macet Pada Koperasi Simpan Pinjam Primer Koperasi Purnawirawan Abri (Primkopabri) Unit Margasari Kecamatan Margasari Kabupaten Tegal - Karlina Karlina; Roni Roni; Nasiruddin Nasiruddin (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the influence of debtor characteristics, the influence of interest rates, and the influence of loan terms on bad credit at the Primkopabri Savings and Loans Cooperative, Margasari Unit, Margasari District, Tegal Regency. This research method is quantitative with data analysis using multiple linear regression. The research population was 139 Cooperative members, using the Slovin formula to obtain a sample of 58. The results of the research that has been carried out show that; Debtor characteristics have a significant positive effect on Bad Credit as indicated by a coefficient value of 0.402 and a significance value of 0.000 which is smaller than 0.05 or 0.000 < 0.05. Interest Rates have a significant negative effect on Bad Credit with a coefficient value of -0.705 and a significance value of 0.000 which is smaller than 0.05 or 0.000 < 0.05. Meanwhile, the Loan Term has a significant positive effect on Bad Credit with a coefficient value of 0.327 and a significance value of 0.009 which is smaller than 0.05 or 0.009 < 0.05. The results of this research show that all independent variables tested have a significant effect on bad credit.